Classification of Osteosarcoma Based on Immunogenomic Profiling - Wang, Xinwen; Wang, Liangming; Xu, Weifeng; Wang, Xinwu; Ke, Dianshan; Lin, Jinluan; Lin, Wanzun; Bai, Xiaochun (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence has supported that osteosarcoma is heterogeneous, and several subtypes have been identified based on the genomic profiling. Immunotherapy is revolutionizing cancer treatment and is a promising therapeutic strategy. Whereas, few studies have identified osteosarcoma classification based on immune biosignatures, which offer the optimal stratification of individuals befitting immunotherapy. Here, we classified osteosarcoma into two clusters: immunity high and immunity low using the single-sample gene-set enrichment analysis (ssGSEA) and unsupervised hierarchical clustering. Immunity_H subtype was associated with high immune cells infiltration, a favorable prognosis, benefit to immunotherapy, high HLA genes expression, and activated immune signal pathway indicating an immune-hot phenotype. On the contrary, Immunity_L subtype was correlated with low immune cells infiltration, poor prognosis, and cancer-related pathway indicating an immune-cold phenotype. We also identified TYROBP as a key immunoregulatory gene that associated with CD8+ T cell infiltration by multiplex immunohistochemistry (mIHC). Finally, we established an immune-related prognostic model that predicted the survival time of osteosarcoma. In conclusion, we established a new classification system of osteosarcoma based on immune signatures and identified TYROBP as a key immunoregulatory gene. This stratification had significant clinical outcomes for estimating prognosis, as well as the immunotherapy of osteosarcoma patients.